ICT and the tension between old and new: the human factor - Gorniak-Kocikowska, Krystyna (Journal of Information, Communication and Ethics in Society, 2008)
Purpose The purpose of this paper is to deepen the understanding of tensions between old and new in the emerging global society driven by information and communication technology (ICT); and to argue that creation of a theory of this society would contribute in the easing of these tensions. Design/methodology/approach The methods used in this paper are mostly analytical, descriptive, and qualitative. An analysis of the creation and development of ICT from a mathematical discipline of computer science to a universal tool and a driving force of the emerging global society, a development which is paralleled by the commercialization of ICT, is followed by two case studies illustrating the tensions between old and new and the role ICT plays in them. One case is centered on the challenges of traditional models of education by new, ICT-friendly approaches, like the Multiple Intelligences Theory; the other addresses tensions between old and new that in many societies presently take the form of tensions between local/national and global. Findings A claim is formed that the existing tensions between old and new are closely linked to the tensions between the two most common forms of society, inclusive (egalitarian) and exclusive (elitist). Originality/value The paper will help understand some of the reactions to the process of globalization. It can serve as a tool for assessment and prediction regarding this process. Lastly, the paper contains a justification of merit in the creation of a “grass root” theory of an ICT-driven global society built on a universally accepted ethical foundation. © 2008, Emerald Group Publishing Limited
Keywords: Communication technologies; Education; Ethics; Globalization; Information society; Language; dept.phi; peer-reviewed

From computer ethics to the ethics of global ICT society - Gorniak-Kocikowska, Krystyna (Library Hi Tech, 2007)
Purpose - The purpose of this paper is to address the place of computer/ICT ethics in the global ICT society driven by knowledge economy. Design/methodology/approach - The paper focuses on three main issues: the evolution of the name of the leading technology of our times and, accordingly, the evolution of the name of the society in which this technology plays the leading role; some ethical dilemmas that the global ICT society will need to solve; global ICT ethics and the knowledge economy. Findings - The paper suggests that global ICT ethics should be an ethics focusing on the dynamics of the relationship between the weak and the strong, the rich and the poor, the healthy and the sick worldwide - and it should explore the ethical problems from the point of view of both parties involved. That way, Global ICT Ethics can have a truly communicative character, and it can become an ethics that will be both a co-creator and also a result of a democratic processes. Originality/value - This paper should interest anyone concerned with ICT and globalization.
Keywords: Communication technologies; Ethics; Globalization; dept.phi; peer-reviewed